Relationship lending, trust, and SME bank financing in the UK - Hans Degryse; Kent Matthews; Tianshu Zhao (Cardiff University, Cardiff Business School, 2021)
It is well recognized that relationship banking helps to relieve the credit constraints faced by SMEs to access bank finance. Trust is an important part of relationship banking. However, the term trust is nebulous, and relationship banking means different things to different banks and different borrowers. How trust enables the credit market for SMEs through relationship banking is largely unexplored. Using a unique primary dataset of SMEs in the UK, we construct a measure of trust-based relationship banking from the perspective of the borrower. We examine the drivers of trust-based relationship banking in terms of organizational trust in the relationship manager, defined as the delegation of operational autonomy, along with local market and social capital factors, and the style of the bank-borrower relationship. Along with bank, firm, and market factors, trust-based relationship banking helped to reduce the credit constraints faced by SMEs in the decade following the global financial crisis.
Keywords: G21; G29; L14; 330; Trust; Relationship Banking; SME Financing; Bank Organization